Identification of Susceptibility Genes of Adult Asthma in French Canadian Women. (4th May 2016) - Bérubé, Jean-Christophe; Gaudreault, Nathalie; Lavoie-Charland, Emilie; Sbarra, Laura; Henry, Cyndi; Madore, Anne-Marie; Paré, Peter D.; van den Berge, Maarten; Nickle, David; Laviolette, Michel; Laprise, Catherine; Boulet, Louis-Philippe; et al.
Abstract : Susceptibility genes of asthma may be more successfully identified by studying subgroups of phenotypically similar asthma patients. This study aims to identify single nucleotide polymorphisms (SNPs) associated with asthma in French Canadian adult women. A pooling-based genome-wide association study was performed in 240 allergic asthmatic and 120 allergic nonasthmatic women. The top associated SNPs were selected for individual genotyping in an extended cohort of 349 asthmatic and 261 nonasthmatic women. The functional impact of asthma-associated SNPs was investigated in a lung expression quantitative trait loci (eQTL) mapping study (n = 1035 ). Twenty-one of the 38 SNPs tested by individual genotyping showed P values lower than 0.05 for association with asthma. Cis -eQTL analyses supported the functional contribution of rs17801353 associated with C3AR1 (P = 7.90 E - 10 ). The asthma risk allele for rs17801353 is associated with higher mRNA expression levels of C3AR1 in lung tissue. In silico functional characterization of the asthma-associated SNPs also supported the contribution of C3AR1 and additional genes including SYNE1, LINGO2, and IFNG-AS1 . This pooling-based GWAS in French Canadian adult women followed by lung eQTL mapping suggested C3AR1 as a functional locus associated with asthma. Additional susceptibility genes were suggested in this homogenous subgroup of asthma patients.